Effect of Subcooling on Thermal Performance of Organic Rankine Cycle With Zeotropic Mixture in Geothermal Power Generation - Ran CHEN; Qiang LIU; Dongyu MENG (发电技术)
Organic Rankine cycle (ORC) is the main way to generate electricity by using medium-low temperature (< 150℃) geothermal heat. In actual operation, zeotropic mixture tends to condense to the subcooling state. This paper analyzed the effect of subcooling on thermal performance of ORCs using zeotropic mixture as working fluid. The mathematics model of the ORC and the ORC with internal heat exchanger (IHE) were established, and then the evaporation pressure was optimized to maximize the net power output. Moreover, the system exergy analysis was also conducted. The results show that the condensation subcooling affects the temperature profile match between the working fluid and the heat sink. Limited by the pinch point temperature difference, the condensation pressure rises with the subcooling increasing. The subcooling also changes the heat allocation between the preheater and evaporator, the optimal evaporation pressure also increases as the subcooling increases. When the subcooling is 2℃, the net power output can be reduced by 4.36% for isobutene/isopentane (0.4:0.6) which is the most affected by the subcooling. The IHE recovers the waste heat of expander exhaust to preheat the working fluid, as a result, the net power output of the subcooled ORC system can be increased by 0.55%. The subcooling causes a significant increase in the condenser exergy destruction that can be reduced by 24.7% using the recuperative ORC system.